Cuerpos rebeldes, memoria viva: Sobre la performatividad de los “tropeles” en la Universidad Nacional de Colombia - Männich, Leonie (Notas de Antropología de las Américas, 2025)
This paper presents an analysis of the organized “tropeles” that can be observed at the entrances to the campus of the National University in Colombia. It puts forth an understanding of them as a bodily practice that beyond its form as a violent encounter and based on anthropological theories on rituals/performances allows us to see its form as a practice of collective memory and to recognize its subversive potential stimulating reflection processes for a politically committed anthropology.